2022
DOI: 10.3390/ijms231911549
|View full text |Cite
|
Sign up to set email alerts
|

A Previously Unrecognized Molecular Landscape of Lynch Syndrome in the Mexican Population

Abstract: Lynch syndrome (LS) is the main hereditary colorectal cancer syndrome. There have been few reports regarding the clinical and molecular characteristics of LS patients in Latin America; this is particularly true in the Mexican population, where no information is available. The present study aims to describe the clinical and molecular spectrum of variants in a cohort of patients diagnosed with LS in Mexico. We present a retrospective analysis of 412 patients with suspected LS, whose main site of cancer diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This variant was first described by Moslein et al in 1996 [ 27 ] and it was later reported in other populations from Europe, Asia, Africa, North America, and Argentina ( Supplementary Table 1 ). It has also been reported in Mexican individuals living in the United States [ 11 ] and was found to be a recurrent variant in a previous report of LS in Mexico [ 25 ]. Fig.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This variant was first described by Moslein et al in 1996 [ 27 ] and it was later reported in other populations from Europe, Asia, Africa, North America, and Argentina ( Supplementary Table 1 ). It has also been reported in Mexican individuals living in the United States [ 11 ] and was found to be a recurrent variant in a previous report of LS in Mexico [ 25 ]. Fig.…”
Section: Discussionmentioning
confidence: 57%
“…Only eight studies have reported data on Mexican-Mestizo patients with molecularly confirmed LS [ 5 , 8 , [20] , [21] , [22] , [23] , [24] , [25] ] shown in Table 4 . In the present study, the MLH1 gene (67.5 %) was more frequently affected than MSH2 (22.5 %).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they could have tabled the TNM staging of the tumor at the time of diagnosis similar to the study conducted by Padua et al in 2022. 3 Additionally, we feel that insight into the treatment regimens and duration of chemotherapy or immunotherapy would have augmented the quality of this paper. For instance, a 2022 study summarized the medical and surgical procedures that each of the four identified patients underwent.…”
Section: Comment On: Clinical and Molecular Features Of Pediatric Can...mentioning
confidence: 99%